Sudden Cardiac Death in Adolescent Athletes and the Role of Genetic Screening : A Literature Review - Ami Febby Triani; Gusril Gusril; Arsil Arsil; Ronni Yenes; Adri Budiwanto; Yovhandra Ockta (Jurnal Penelitian Pendidikan IPA, 2023)
Sudden death, particularly among seemingly healthy individuals, presents a critical challenge in both medical and athletic communities. This literature review investigates sudden cardiac death (SCD) in adolescent athletes, emphasizing the role of genetic screening. Utilizing various studies from 2019 to 2024, the review highlights that SCD, while rare, often stems from cardiovascular issues such as cardiomyopathy and coronary artery anomalies. Pre-participation screening, including ECGs, is crucial in identifying at-risk individuals, yet raises ethical debates regarding athlete disqualification. Genetic factors play a significant role, with inherited heart conditions frequently implicated in SCD cases. Comprehensive genetic screening and family evaluations are vital, although widespread implementation is hindered by limited positive outcomes and potential psychosocial effects. Epidemiological studies reveal a higher incidence of SCD during competitive sports, underscoring the need for tailored prevention strategies. Findings emphasize the importance of multidisciplinary collaboration in enhancing screening methods, risk assessment, and preventive interventions to mitigate sudden mortality in young athletes. The study concludes that lifestyle modifications, promoted by health organizations, and advancements in genetic diagnosis are essential in improving the health and safety of athletes. Efforts to integrate cardiovascular and genetic screening into clinical and athletic practice are paramount, aiming to reduce the incidence of SCD and enhance the well-being of young athletes globally.